Representation of mental illness in video games beyond stigmatization - Kasdorf, Ruth (Frontiers in Human Dynamics, 2023)
The representation of mental illness is part of many video games; however, it is often accompanied by stigmatization of and discrimination against those who are affected. Recently, a more positive approach has been found, including a dimensional representation of mental disorders such as depression or anxiety, especially in games developed by independent developers. The study examined the most popular video games of 2018 and 2019 based on their representation of mental illness in a mixed-methods approach. A quantitative coding process examining general aspects of the games, the characters affected, and the illness representation is followed by a qualitative video game analysis of the games in the sample with a dimensional representation of mental illness. It was found that 16 of the 74 games examined included characters who were affected by mental illnesses. For the most part, mental illness is an essential aspect of the games analyzed in the sample represented by the main characters. However, the depiction of mental illness often lacks depth and dimensionality. Two examples in the study offer a dimensional representation that includes mental illness as characters, as part of the environment and atmosphere, and provides illness-related advice as part of the gameplay. These findings can be helpful for developing games with the potential to reduce discrimination and stigmatization of mental illness and those affected in the future by pointing out aspects leading to a more dimensional and empathetic portrayal of mental illness in existing games. Additionally, the category system used in this study is adaptable to future qualitative research on mental illness representation in video games.